The Influence of Inspiring Leadership and Religiosity on Teacher Performance - Norman, Efrita; Paramansyah, Arman; Zaini, Abdul Wahid (JURNAL AL-TANZIM, 2024)
The research focuses on the influence of inspiring leadership and religiosity on teacher performance at SMAN 2 Kota Bogor. Using a correlational approach, this quantitative research aims to identify the relationship between inspiring leadership and religiosity and teacher performance without intervention. Using this approach, this study seeks to provide a deeper understanding of the psychological dynamics involved in educational contexts. Data collection was conducted through que to measure teachers' perceptions of inspiring leadership and the level of individual religiosity, as well as in-depth interviews to gain a qualitative understanding of teachers' experiences in interactions with school leaders and expressions of religiosity. Data analysis used validity and reliability tests, multiple linear regression, and t and F values testing to assess the significance of the influence of independent variables on teacher performance. Data analysis revealed that inspiring leadership and religiosity played a significant role in improving teacher performance, with all question items in both variables showing strong validity and high levels of reliability. The implications of this research highlight the urgency of inspiring leadership and increasing understanding of spirituality in educational contexts to effectively improve teacher performance.